Drug Repurposing Screen Identifies Foxo1-Dependent Angiopoietin-2 Regulation in Sepsis*. Issue 7 (July 2015) - Ghosh, Chandra C.; Thamm, Kristina; Berghelli, Anthony V.; Schrimpf, Claudia; Maski, Manish R.; Abid, Tanaz; Milam, Katelyn E.; Rajakumar, Augustine; Santel, Ansgar; Kielstein, Jan T.; Ahmed, Asif; Thickett, David; et al.
Abstract : Objective: The recent withdrawal of a targeted sepsis therapy has diminished pharmaceutical enthusiasm for developing novel drugs for the treatment of sepsis. Angiopoietin-2 is an endothelial-derived protein that potentiates vascular inflammation and leakage and may be involved in sepsis pathogenesis. We screened approved compounds for putative inhibitors of angiopoietin-2 production and investigated underlying molecular mechanisms. Design: Laboratory and animal research plus prospective placebo-controlled randomized controlled trial (NCT00529139) and retrospective analysis (NCT00676897). Setting: Research laboratories of Hannover Medical School and Harvard Medical School. Patients: Septic patients/C57Bl/6 mice and human endothelial cells. Interventions: Food and Drug Administration–approved library screening. Measurements and Main Results: In a cell-based screen of more than 650 Food and Drug Administration–approved compounds, we identified multiple members of the 3-hydroxy-3-methyl-glutaryl-CoA reductase inhibitor drug class (referred to as statins) that suppressed angiopoietin-2. Simvastatin inhibited 3-hydroxy-3-methyl-glutaryl-CoA reductase, which in turn activated PI3K-kinase. Downstream of this signaling, PI3K-dependent phosphorylation of the transcription factor Foxo1 at key amino acids inhibited its ability to shuttle to the nucleus and bind cis -elements in the angiopoietin-2 promoter. In septic mice, transient inhibition of angiopoietin-2 expression by liposomal siRNA in vivo improved absolute survival by 50%. Simvastatin had a similar effect, but the combination of angiopoietin-2 siRNA and simvastatin showed no additive benefit. To verify the link between statins and angiopoietin-2 in humans, we performed a pilot matched case-control study and a small randomized placebo-controlled trial demonstrating beneficial effects on angiopoietin-2. Conclusions: 3-hydroxy-3-methyl-glutaryl-CoA reductase inhibitors may operate through a novel Foxo1-angiopoietin-2 mechanism to suppress de novo production of angiopoietin-2 and thereby ameliorate manifestations of sepsis. Given angiopoietin-2's dual role as a biomarker and candidate disease mediator, early serum angiopoietin-2 measurement may serve as a stratification tool for future trials of drugs targeting vascular leakage. Abstract : Supplemental Digital Content is available in the text.